2010
DOI: 10.1103/physrevb.81.020501
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature transition to a superconducting phase in boron-doped silicon films grown on (001)-oriented silicon wafers

Abstract: International audienceWe report on a detailed analysis of the superconducting properties of boron-doped silicon films grown along the 001 direction by gas immersion laser doping. The doping concentration c(B) has been varied up to similar to 10 at. % by increasing the number of laser shots to 500. No superconductivity could be observed down to 40 mK for doping level below similar to 2 at. %. The critical temperature T(c) then increased steeply to reach similar to 0.6 K for c(B) similar to 8 at. %. No hysteresi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 19 publications
7
56
2
Order By: Relevance
“…We find that the qualitative doping dependence of Ge:Ga is in good agreement with previous observations in BDD and Si:B [7,9]. Also the critical hole concentrations of 0.5 at.% (0.9·10 21 cm -3 ) [9] in BDD and 2 at.% (1·10 21 cm -3 ) [7] in Si:B are comparable to our finding of 0.4 at.% (0.2·10 21 cm -3 ) in Ge:Ga. However, a quantitative description in terms of an universal understanding requires further knowledge about the role of the dopants.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We find that the qualitative doping dependence of Ge:Ga is in good agreement with previous observations in BDD and Si:B [7,9]. Also the critical hole concentrations of 0.5 at.% (0.9·10 21 cm -3 ) [9] in BDD and 2 at.% (1·10 21 cm -3 ) [7] in Si:B are comparable to our finding of 0.4 at.% (0.2·10 21 cm -3 ) in Ge:Ga. However, a quantitative description in terms of an universal understanding requires further knowledge about the role of the dopants.…”
Section: Discussionsupporting
confidence: 80%
“…It was found that above a certain concentration, usually tagged as critical doping level, superconductivity emerges. Close to this point, T c rises steeply and seems to saturate at higher concentrations [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In both cases, superconductivity develops in the partially unfilled valence band for boron concentrations n B ∼ 10 21 cm −3 and most probably originates from a standard electron-phonon coupling mechanism. The critical temperature reaches T c ∼ 0.6 K in Si:B 4 but rises up to ∼10 K in C:B 5 due to a better coupling potential in this lighter element (for a review see Ref. 6).…”
Section: Introductionmentioning
confidence: 99%